Fiber-dependent injection molding simulation of discontinuous reinforced polymers - Wittemann, Florian (Karlsruher Schriftenreihe Fahrzeugsystemtechnik, 2022)
This work presents novel simulation techniques for injection molding of fiber reinforced polymers. These include approaches for anisotropic flow modeling, hydrodynamic forces from fluid on fibers, contact forces between fibers, a novel fiber breakage modeling approach and anisotropic warpage analysis. Due to the coupling of fiber breakage and anisotropic flow modeling, the fiber breakage directly influences the modeled cavity pressure, which is validated with experimental data.